Comparison of fattening performance of limousine, charolais, angus and hereford breed bulls - Tamer Kayar; Şeref İnal (Eurasian Journal of Veterinary Sciences)
Aim: This research was conducted to compare the fattening performances of Limousine, Charolais, Angus and Hereford breed calves imported to Turkey. Materials and Methods: A total of 200 male fattening calves, aged 10-12 months were used as animal material. The calves were fed ad libitum for 24 weeks of fattening. During the first 12 weeks of fattening, the animals were given fattening development feed with 14.26% crude protein (CP) and 2637 kcal / kg metabolic energy (ME) and in the last 12 weeks, they were given fattening completion feed with 14.11% CP and 2744 kcal / kg ME. The fattening period was completed on the 168th day of the study (24 weeks). Results: Significant differences were observed among groups in terms of live weight, growth rate and feed consumption. Although the Charolais had the lowest weight at the beginning of the fattening, they reached the highest weight gain with the highest daily live weight at the end. A similar relationship was observed between the Charolais and Herefords in terms of growth performance. Conclusion: In this study, it can be concluded that Charolais and Hereford breed calves would be more profitable than others to be imported to Turkey for fattening. On the other hand, to get more accurate results, more research needs to be done about cattle breeds imported to Turkey.